Early pheromone perception remodels neurodevelopment and accelerates neurodegeneration in adult C. elegans - Jing-Yi Peng; Xuqing Liu; Xian-Ting Zeng; Yue Hao; Jia-Hui Zhang; Qian Li; Xia-Jing Tong (Cell Reports, 2023)
Summary: Age-associated neurodegenerative disorders such as Parkinson’s and Alzheimer’s diseases are mainly caused by protein aggregation. The etiologies of these neurodegenerative diseases share a chemical environment. However, how chemical cues modulate neurodegeneration remains unclear. Here, we found that in Caenorhabditis elegans, exposure to pheromones in the L1 stage accelerates neurodegeneration in adults. Perception of pheromones ascr#3 and ascr#10 is mediated by chemosensory neurons ASK and ASI. ascr#3 perceived by G protein-coupled receptor (GPCR) DAF-38 in ASK activates glutamatergic transmission into AIA interneurons. ascr#10 perceived by GPCR STR-2 in ASI activates the secretion of neuropeptide NLP-1, which binds to the NPR-11 receptor in AIA. Activation of both ASI and ASK is required and sufficient to remodel neurodevelopment via AIA, which triggers insulin-like signaling and inhibits autophagy in adult neurons non-cell-autonomously. Our work reveals how pheromone perception at the early developmental stage modulates neurodegeneration in adults and provides insights into how the external environment impacts neurodegenerative diseases.